PEMBERDAYAAN KELOMPOK DASAWISMA DALAM PEMANFAATAN DAUN KOKANG (Lepisanthes amona (HASSK) LEENH.) SEBAGAI PRODUK KECANTIKAN - Rohmah, Miftakhur; Andriyani, Yulian; Widuri, Nike (Universitas Mataram, 2024)
This community service program aimed to empower the Dasawisma group in Kota Bangun I Village through the utilization of kokang leaves (Lepisanthes amoena) as raw material for beauty products. The training was conducted in several stages, including the identification of the bioactive potential of kokang leaves, drying techniques using a dehydrator, rice fermentation for cold powder production, packaging, and product labeling. The results showed a significant increase in participants' understanding and skills in processing kokang leaves into value-added products. The products were successfully marketed through local exhibitions and competitions. In addition, continuous assistance through the WhatsApp group ensured the sustainability of the production. This program is expected to improve the local economy by optimally utilizing the village's natural resources.